Manajemen Sumber Daya Manusia Berbasis Masjid di SDIT Masjid Raya Lantai Batu Kabupaten Tanah Datar - Arlen, Arlen; Jamilus, Jamilus (Mimbar Kampus: Jurnal Pendidikan dan Agama Islam, 2024)
Human resources are an important factor in achieving the goals of an organization including schools. Existing human resources need to be managed so that they become optimal resources. Human resource management starts from the process of planning, empowering and supervising human resources. This research was conducted at SDIT Masjid Raya Floor Batu, Tanah Datar District using a qualitative descriptive method where research data were obtained from interviews with school principals and foundation supervisors. The results of this study indicate that the resource management carried out at SDIT Masjid Raya Floor Batu, Tanah Datar Regency is mosque-based management which starts from planning, empowering and supervising it. All systems, starting from weakening teachers and education staff, optimizing resources with various trainings and also supervision from school principals as well as foundation supervisors and education service supervisors have been running well. All processes carried out are oriented towards the mosque which is one of the pillars of this school. Keywords: Management, Human Resources, Mosque Based